Evaluation Of The Implementation Of The SELEDRI Policy Towards E-Government - Haryaningsih, Sri; Yohanes, Yulius; Andriani, Farah Devi; Elyta, Elyta (Universitas Dharma Wacana, 2023)
Presidential Instruction No. 3 of 2003 about national policies and goals for e-government development shows the government's commitment to using information technology (IT) infrastructure to carry out government functions. Under Presidential Instruction No. 3 of 2003, the government directed various government agency officials, including governors and regents/mayors, to carry out measures to implement e-Government on a national scale. They were also instructed to develop and execute subsequent plans, collaborate with the Minister of State for Communications and Information, and ensure the president's instructions were implemented to the best of their abilities. This study focuses on identifying and addressing issues, therefore the researcher aims to understand the elements that affect the implementation of the SELEDRI programme, which has not been effective in building e-government at the Population and Civil Registration Service of Kubu Raya Regency. The researcher's choice of research method aligns with the research objectives. numerical Since it employs a method. This study employs the idea of George C. Edward Edward III, who argues that policy implementation is affected by Communication, Resources, Disposition, and Bureaucratic Structure. Thus, academics aim to do study on assessing the degree of success in Policy implementation SELEDRI